Pelatihan Inovasi Kuliner Berbasis Bahan Pangan Lokal: Membangun Produk Makanan Berkualitas dan Berdaya Saing di Desa Bubunan, Buleleng - Hendrayana , Made; Atmaja, I Made Purwa Dana; Trisdayanti, Ni Putu Eka; Rumadana, I Made; Pujawan, Anak Agung Ketut Alit; Martadjaya, I Gusti Made Iwan Dusanta; Sudiarta, Ngakan Putu; Dalem, Anak Agung Gd Putra K.P; Sunada, I Nyoman; Kristiana, Nina Indra; Kartini, Luh Putu; Winata, Gede Adi Sistha; Hardina (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2025)
Bubunan Village has great potential in the agricultural sector, especially in the availability of local food ingredients such as cassava, corn and sweet potatoes. However, this potential has not been utilized optimally by the local community. Limited knowledge and skills in processing food into value-added products is one of the main obstacles faced. This community service activity aims to increase the capacity of the Bubunan Village community in processing local food ingredients into innovative food products that have economic value. The methods used in this activity include identification of local food ingredients, socialization and recruitment of participants, training in the theory and practice of food processing. This training emphasizes the importance of hygienic processing, product innovation, and effective marketing strategies. It is hoped that the results of this activity will be able to increase the community's skills and knowledge in food processing, as well as encourage the creation of local food products that are competitive in the market. With this training, it is hoped that there will be an increase in the income and welfare of the people of Bubunan Village, as well as strengthening the local economy through utilizing the potential of existing natural resources. Evaluation of this program shows an increase in product quality and entrepreneurial spirit among participants, which is expected to be sustainable and provide long-term benefits for village communities.